Optimal control of biomechanical motion using physiologically motivated cost functions - Maas, Ramona; Leyendecker, Sigrid (Proceedings of the 2nd Joint International Conference on Multibody System Dynamics, 2012)
Ordinary and well-trained human motion is mostly planned and controlled unconsciously by the central nervous system (CNS). Therefore, it is an interesting topic to learn and understand more about human control mechanisms, especially with regard to improve protheses or athletic motion. In this context we use rigid multibody systems to represent bones and joints and formulate an optimal control problem (OCP) with the goal to minimise a physiologically motivated cost function. We compare several cost functions known from literature to a another cost function concerning the impact on the joints involving the constraint forces. A direct transcription method called DMOCC is used to solve the OCP, whereby we benefit from it’s structure preserving formulation as the resulting optimal discrete trajectories are symplectic-momentum preserving
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.ltd.optima_8